Reasons and Consequences of Low Level of Financial Inclusion of People with Disabilities and Deterioration the Situation during Pandemic Covid-19 - FRĄCZEK Bożena (Communications of International Proceedings, 2021)
Worldwide, people with disabilities experience worse socioeconomic outcomes such as less education, poorer health outcomes, lower levels of employment, higher poverty rates and lower level of financial inclusion in comparison to the population without disabilities. The aim of this paper is to present the very important contemporary problem of the poor economic situation of people with disabilities as constituting the main reason for their low level of financial inclusion, as well as to present the consequences of limited access and usage of basic financial products and services by this vulnerable group. The special attention was paid to deterioration the economic situation of this group during pandemic Covid-19.
Keywords: Financial Inclusion; Disability; Discrimination; Diversity